Rahn Contract at Sharia Pawnshop in Madura: Analysis of Maqasid al-Shariah, Socio-Cultural Dynamics, and Socio-Economic Impacts - Fauzi, Nur; Humaidi; Ali, Mohammad Mahbubi (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This study examines the implementation of the Rahn contract at Sharia Pawnshops in Madura, focusing on its alignment with the principles of Maqasid al-Shariah, the socio-cultural and religious dynamics influencing perceptions and implementation, as well as the resulting socio-economic impacts. The study is motivated by academic debates regarding the effectiveness of Islamic financial instruments in achieving societal welfare goals. Using a qualitative approach and a case study method, the research gathers data through in-depth interviews, participatory observation, and document analysis. The findings indicate that, in general, the Rahn contract at Sharia Pawnshops in Madura has fulfilled the objectives of Maqasid al-Shariah, particularly in terms of asset protection (hifz al-mal) and social welfare. However, its implementation still faces challenges, especially regarding transparency and financial literacy among the public. Furthermore, the socio-cultural and religious dynamics in Madura play a significant role in shaping public perceptions of Rahn, where local wisdom values and religious norms influence the use of Sharia pawnshop services. From a socio-economic impact perspective, the study finds that Sharia Pawnshops contribute to increased financial inclusion, better access to capital for small businesses, and a reduction in reliance on the conventional interest-based pawn system. However, there are some challenges, such as administrative fees that are still perceived as high by some members of the community and limited access in remote areas. These findings provide valuable insights for developing a more inclusive Rahn system that aligns with local community needs. Policy recommendations include enhancing Sharia financial education, optimizing Rahn-based financing schemes, and strengthening regulations to ensure transparency and sustainability for Sharia Pawnshops in Madura.